Cultural transformation in the digital world - Singapore Management University (Institutional Knowledge at Singapore Management University, 2018)
The context of businesses across the world is fast changing – more specifically, Digitalisation has had a growing and increasingly disruptive impact across industry sectors and regions. Companies in the APAC region, like many others across the world, are grappling with the digital wave and its implications for their own structures, strategies and people. It appears that many are struggling to cope with the phenomenon, only a few have been able to embrace it fully, and almost none have been able to get ahead of it, proactively. Although much has been written and said about Digitalisation in the Asian context, our team believed that it was necessary to gain a much deeper understanding of what Digitalisation meant to companies in Asia and beyond, how it was being perceived by C-Suite leaders as well as the rest of the organisation, and what is being done to prepare their organisations and people for the changes that are needed for future success. The topical nature of the subject, as well as the high priority being accorded to it by several companies in Asia and across the world, inspired us to delve deeper into the subject, and undertake this evidence-based study. We hope that our efforts and findings will benefit the broader business community as it “muddles through” its own responses to Digitalisation.